Indonesian Netizens’ Digital Self and Identity Creation on Social Media - Dwi Susanti; Prihatin Dwi Hantoro (Komunikator, 2022)
Users’ identity is important in accessing social media and digital platforms. This identity is formed and accessed digitally and can serve to identify fellow users of the platform. Digital identity can be in two forms: partial and social. Identity in social media is important because this is the main thing that needs to be done before users can carry out activities such as uploading and commenting on their own accounts. This study aims to identify how users respond to the creation of a user's digital identity on social media. This study uses a descriptive quantitative method with a survey method involving 218 respondents of various ages, occupations, and forms of access to social media. The data collection process was carried out in August-September 2022. The results of this study indicate that in creating a partial digital identity, most users display personal data that is the same as their identity in the real world. Then on account ownership, most users gave an approval response to the ownership of more than one account on their social media. Finally, users' self-disclosure on social media is carried out through a selection process on activities that are shared publicly and privately through their social media accounts.